Beneficial role of vitexin in Parkinsons disease - Mustapha, Musa; Mat taib, Che Norma (Penerbit Universiti Sains Malaysia, Universiti Sains Malaysia Press, 2023)
Today, Parkinsons disease (PD) is the foremost neurological disorder all across the globe. In the quest for a novel therapeutic agent for PD with a multimodal mechanism of action and relatively better safety profile, natural flavonoids are now receiving greater attention as a potential source of neuroprotection. Vitexin have been shown to exhibit diverse biological benefits in various disease conditions, including PD. It exerts its anti-oxidative property in PD patients by either directly scavenging reactive oxygen species (ROS) or by upregulating the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and enhancing the activities of antioxidant enzymes. Also, vitexin activates the ERK1/1 and phosphatidyl inositol-3 kinase/ Akt (PI3K/Akt) pro-survival signalling pathway, which upregulates the release of anti-apoptotic proteins and downregulates the expression of pro-apoptotic proteins. It could be antagonistic to protein misfolding and aggregation. Studies have shown that it can also act as an inhibitor of monoamine oxidase B (MAO-B) enzyme, thereby increasing striatal dopamine levels, and hence, restoring the behavioural deficit in experimental PD models. Such promising pharmacological potential of vitexin could be a game-changer in devising novel therapeutic strategies against PD. This review discusses the chemistry, properties, sources, bioavailability and safety profile of vitexin. The possible molecular mechanisms underlying the neuroprotective action of vitexin in the pathogenesis of PD alongside its therapeutic potential is also discussed.